The perception of government valuers on the current practice of heritage property valuation / Nuriza Mohd Narawi and Junainah Mohamad - Mohd Narawi, Nuriza; Mohamad, Junainah (2018)
This paper studies the perception of government valuers on the current practice of heritage property valuation. This paper focuses on identifying the challenges faced by the valuers; factors affecting the value of heritage property; and the methods used by valuers in valuing the heritage property. To achieve the aim of this study, interviews were conducted with selected valuers from the Ipoh Valuation and Property Services Department, Manjung Municipal Council and Batu Gajah District Council. The qualitative approach was chosen for the data collection process. The content analysis method was used in analysing the data from the respondents. The findings show that the historical factors affecting the values of heritage property were not considered in valuing the heritage property, and the method commonly used by valuers was the sale comparison approach. The interviewees also admitted that there are challenges existing in undertaking an assessment of heritage property such as lack of knowledge, economic factors, legislation factors, condition of the building and safety (threats from homeless persons and wild animals).